Democracy, Market Economics and Development : An Asian Perspective - Igbal, Farrukh; You, Jong-Il (Washington, DC: World Bank, 2013)
The book contains a selection of papers presented at the Conference on Democracy, Market Economy, and Development, whose objective was to examine the extent of which democracy is important to the achievement of sustainable development. While it is widely accepted that economic freedom, as ensured broadly by the operation of the economy according to market, or laissez-faire principles, is a critical determinant of development, the role of political freedom, as ensured broadly by the practice of democracy, is less well understood. The papers focus largely on the experience of East Asia in recent years, featuring: democracy and the market economy, emphasizing both politics, and economics as essential to improve the lives of citizens; democracy and social justice, as intrinsic to development, arguing that rights and liberties are best conveyed by the democratic system of governance; participation, as fundamental to democracy and development, for it is the practice of democracy that is most critical to the long-term sustainability of development; liberal participatory democracy, as instrumental to prod sustainable economic reforms, by ensuring the legitimacy of reform efforts. Notably, the preconditions that participatory democracy requires in order to fully support reforms, are discussed, with supporting evidence from experiences in Latin America, and Asia; and, political and economic institutions of Asia, and the West, as set to converge, despite inconclusive debates on Asian values.